Temporal, Spatial and Prey Niche Partitioning Reveals Coexistence Mechanism of Mesocarnivores in Guangdong Province, South China - Fei Wu; Yan Hua; Hongliang Dou; Yulin Zhang; Xiaoxin Dong; Di Zhu; Haiyang Gao (Ecology and Evolution, 2025)
ABSTRACT Mesocarnivores are expected to maintain ecosystem function and stability as emerging apex predators after the decline and extinction of large carnivores. However, we still do not fully understand the mechanisms by which sympatrically distributed mesocarnivores coexist. Niche partitioning provides a fundamental explanation, yet most studies focus on only temporal and spatial dimensions, often overlooking the role of prey resources. To comprehensively understand mesocarnivore coexistence in the context of widespread large carnivore extirpation, we collected camera trap data from four national and sixteen provincial nature reserves in Guangdong Province, South China. We examined the niche partitioning of four mesocarnivores, including leopard cat (Prionailurus bengalensis), masked palm civet (Paguma larvata), spotted linsang (Prionodon pardicolor), and ferret badger (Melogale moschata) across temporal, spatial, and prey resources (murids and three pheasant species) dimensions. Results indicate that mesocarnivores exhibit greater degrees of overlap in temporal niche (Dhat4 index ranges from 0.66 to 0.93), compared to spatial niche (Pianka's O index ranges from 0.03 to 0.44). Prey availability is positively associated with mesocarnivores' RAI (relative abundance index), with the RAI of murids serving as a primary explanatory variable for masked palm civet, spotted linsang, and ferret badger's RAI. The abundance of leopard cat is positively associated with the RAI of silver pheasant (Lophura nycthemera). Abundances of masked palm civet and ferret badger show species‐specific associations with the RAI of white‐necklaced partridge (Arborophila gingica) and Chinese bamboo partridge (Bambusicola thoracicus), respectively. Additionally, the spatiotemporal niche overlap among mesocarnivores remains stable between dry and rainy seasons. We conclude that spatial niche partitioning and diverse utilization patterns of prey resources are likely to facilitate the coexistence of mesocarnivores. Our findings provide a multidimensional perspective on mesocarnivore coexistence mechanisms, offering new insights into their ecological interactions and a reference for the conservation and management of mesocarnivores in Guangdong Province, South China.